Efficacy and Mechanism of Cinnamon Essential Oil on Inhibition of Colletotrichum acutatum Isolated From ‘Hongyang’ Kiwifruit - He, Jingliu; Wu, Dingtao; Zhang, Qing; Chen, Hong; Li, Hongyi; Han, Qiaohong; Lai, Xingyue; Wang, Hong; Wu, Yingxue; Yuan, Jiagen; Dong, Hongming; Qin, Wen (Frontiers in Microbiology, 2018)
In this study, one of the dominant pathogens, which caused postharvest diseases such as anthracnose, was isolated from decayed ‘Hongyang’ kiwifruit. It was identified as Colletotrichum acutatum by its morphological characteristics and standard internal transcribed spacer ribosomal DNA sequence. Further, the efficacy and possible mechanism of cinnamon essential oil on inhibition of C. acutatum were investigated. Results showed that C. acutatum was dose-dependently inhibited by cinnamon essential oil. Meanwhile, the mycelial growth and spore germination of C. acutatum were completely inhibited at the concentrations of 0.200 µL/mL and 0.175 µL/mL (v/v), respectively. Indeed, both minimal inhibitory and minimum fungicidal concentrations of cinnamon essential oil were measured as 0.200 µL/mL. Additionally, the possible antifungal mechanism of cinnamon essential oil on C. acutatum was demonstrated. Results showed that the cinnamon essential oil could destroy the cell membrane integrity of C. acutatum, and the structure of cell membrane was changed. Indeed, the cell cytoplasm including soluble protein, sugar, and nucleic acid was released, which significantly changed the extracellular conductivity. Results suggested that the cinnamon essential oil exerted great potential to be used as a natural and efficient preservative for kiwifruit postharvest storage, which were helpful for the better understanding of the efficacy and mechanism of cinnamon essential oil on inhibition of pathogens isolated from decayed ‘Hongyang’ kiwifruit.